The development and piloting of the REnal specific Advanced Communication Training (REACT) programme to improve Advance Care Planning for renal patients. (April 2014) - Bristowe, Katherine; Shepherd, Kate; Bryan, Liz; Brown, Heather; Carey, Irene; Matthews, Beverley; O'Donoghue, Donal; Vinen, Katie; Murtagh, Fliss EM
Background: In recent years, the End-Stage Kidney Disease population has increased and is ever more frail, elderly and co-morbid. A care-focused approach needs to be incorporated alongside the disease focus, to identify those who are deteriorating and improve communication about preferences and future care. Yet many renal professionals feel unprepared for such discussions. Aim: To develop and pilot a REnal specific Advanced Communication Training (REACT) programme to address the needs of End-Stage Kidney Disease patients and renal professionals. Design: Two-part study: (1) development of the REnal specific Advanced Communication Training programme informed by multi-professional focus group and patient survey and (2) piloting of the programme. Setting/participants: The REnal specific Advanced Communication Training programme was piloted with 16 participants (9 renal nurses/health-care assistants and 7 renal consultants) in two UK teaching hospitals. Results: The focus group identified the need for better information about end-of-life phase, improved awareness of patient perspectives, skills to manage challenging discussions, 'hands on' practice in a safe environment and follow-up to discuss experiences. The patient survey demonstrated a need to improve communication about concerns, treatment plans and decisions. The developed REnal specific Advanced Communication Training programme was acceptable and feasible and was associated with a non-significant increase in confidence in communicating about end-of-life issues (pre-training: 6.6/10, 95% confidence interval: 5.7–7.4; post-training: 6.9/10, 95% confidence interval: 6.1–7.7, unpaired t -test – p = 0.56), maintained at 3 months. Conclusion: There is a need to improve end-of-life care for End-Stage Kidney Disease patients, to enable them to make informed decisions about future care. Challenges include prioritising communication training among service providers.